Composite material for automotive upholstery and preparation process thereof
By using composite materials composed of flame retardant layer and wear-resistant layer in automotive interior materials, the existing automotive interior composite materials have been solved, high flame retardant and wear-resistant properties have been achieved, and antibacterial properties have been achieved.
Patent Information
- Application Number
- CN202411897485.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The existing automotive interior composite materials have poor flame retardancy and poor wear resistance, which may lead to serious burns during fire and affect the aesthetics of the automotive interior.
A composite material consisting of a flame retardant layer and a wear-resistant layer is used. The flame retardant layer is composed of polypropylene fibers, modified polypropylene, glass fibers, flame retardant and antioxidant. The wear-resistant layer is composed of polypropylene, phenolic resin, α-phase nanoalumina, anti-scratch agent and antibacterial additives. The two layers of materials are connected by amino resin coatings.
The flame retardant performance of the material is improved, the limit oxygen index (LOI) is 29.5~34.2, reaching the V-0 flame retardant standard, and at the same time, the wear resistance of the material is enhanced and antibacterial properties are achieved, solving the problem of insufficient flame retardancy and wear resistance of existing automotive interior composite materials.
Smart Images

Figure BDA0005202248040000081 
Figure BDA0005202248040000091 
Figure BDA0005202248040000092
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, in particular to a composite material for automobile interior decoration parts and a preparation process thereof. Background Art
[0002] As a means of transportation for people, cars are closely related to people's lives. With the reduction of car manufacturing costs and the improvement of people's living standards, the selling price of cars has become more affordable. More and more cars have entered people's lives, and the comfort and safety of cars have become the focus of people's attention.
[0003] Car interior refers to two types of car parts with certain decorative, functional, safety, and engineering properties and car products used for car interior modification. Car interior is an important part of the car body. Car interior materials mainly include: leather, rubber, plastic, chemical fiber and composite materials, among which plastic accounts for more than 60% of car interior, and these materials are flammable or combustible materials.
[0004] At the same time, interior materials are distributed in the roof, floor mats, door linings and other parts of the car, and are in close contact with the human body. In the event of a fire, the combustion of interior materials will cause serious burns to the human body. Therefore, improving the flame retardancy of automotive interior materials has great practical significance for improving automotive safety. At the same time, existing automotive interior composite materials have the problems of being not resistant to friction and easy to leave scratches, which affects the beauty of the automotive interior. Therefore, it is of practical significance to provide a composite material with both flame retardancy and good wear resistance. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the deficiencies in the prior art, the present invention provides a composite material for automobile interior decoration parts and a preparation process thereof, which solves the problems of poor flame retardancy and poor wear resistance of the existing composite materials for automobile interior decoration parts.
[0007] (II) Technical solution
[0008] To achieve the above-mentioned purpose, the present invention provides a technical solution: a composite material for automobile interior decoration parts, the composite material is composited by two layers of materials, including an internal flame retardant layer and an external wear-resistant layer, the flame retardant layer and the wear-resistant layer are connected by a coating, the flame retardant layer material includes the following components by mass: 20-40 parts of polypropylene fiber, 10-30 parts of modified polypropylene, 5-10 parts of glass fiber, 1-3 parts of flame retardant, 1-3 parts of deionized water, and 0.1-0.5 parts of antioxidant; the wear-resistant layer includes the following components by mass: 20-30 parts of polypropylene, 5-15 parts of phenolic resin, α-phase nano-alumina, 2-4 parts of anti-scratch agent, 0.5-1 part of silane coupling agent, and 0.05-0.2 parts of antibacterial additive.
[0009] Preferably, the thickness of the flame retardant layer is 1 to 5 mm, the thickness of the wear-resistant layer is 2 to 5 mm, and the connecting layer is an amino resin coating.
[0010] Preferably, the flame retardant comprises the following components by mass: 20-40 parts of lignin, 5-10 parts of expanded graphite, and 5-10 parts of inorganic mineral powder, wherein the inorganic mineral powder comprises one of calcium carbonate, aluminum carbonate, potassium bicarbonate, and magnesium carbonate.
[0011] Preferably, the modified polypropylene is modified by using polypropylene as a base material, using aluminum nitride and silicon powder as nucleating agents, and sodium carboxymethyl cellulose as a thickener, and the modification process includes the following steps:
[0012] Step S01, weighing raw materials, weighing 40-50 parts of polypropylene, 1-3 parts of aluminum nitride, 1-1.5 parts of silicon powder, and 0.1-0.3 parts of sodium carboxymethyl cellulose, wherein the particle sizes of the aluminum nitride, silicon powder, and sodium carboxymethyl cellulose are 2-20 μm;
[0013] Step S02, pretreatment of raw materials: drying the weighed raw materials in an oven at 80° C. for 8 h to remove the existing moisture;
[0014] Step S03, uniformly mixing the prepared polypropylene material with the dried nucleating agent and thickener, and after the samples are uniformly mixed, melt blending is performed in a twin-screw extruder, and extrusion granulation is performed, and injection molding is performed at 200° C. to obtain a modified polypropylene material.
[0015] Preferably, the antioxidant is Si powder, Al powder and B4C, or one of B4C, ZrB2, CaB6, LaB6, MgB2 and AlB2.
[0016] Preferably, the anti-scratch agent comprises the following components by mass: 5 to 10 parts of silicone masterbatch, 2 to 3 parts of graphene, and 1 to 3 parts of polysiloxane; and the antibacterial auxiliary agent is silver ions.
[0017] The present invention provides a technical solution: a process for preparing a composite material for automobile interior decoration parts, wherein the preparation of the composite material comprises the following steps:
[0018] Step S11, preparing a flame retardant layer: weighing 20-40 parts of polypropylene fiber, 10-30 parts of modified polypropylene, 5-10 parts of glass fiber, 1-3 parts of flame retardant, 1-3 parts of deionized water, and 0.1-0.5 parts of antioxidant, mixing them evenly with a high-speed mixer, and then extruding and granulating them with a twin-screw extruder at 190-220° C., and injection molding them at 200° C. to obtain a sheet material 1;
[0019] Step S12, preparing a wear-resistant layer, weighing 20-30 parts of polypropylene, 5-15 parts of phenolic resin, α-phase nano-alumina, 2-4 parts of anti-scratch agent, 0.5-1 part of silane coupling agent, 0.05-0.2 parts of antibacterial additive, and then extruding and granulating them through a twin-screw extruder at 170-190° C., and injection molding at 180° C. to obtain a sheet material 2;
[0020] Step S13, compounding the flame retardant layer and the wear resistant layer: take the sheet materials 1 and 2, apply an amino resin coating on the connection between the materials, and press them together using a tablet press to obtain a composite material.
[0021] Preferably, the wear-resistant layer comprises the following steps:
[0022] Step S21, weighing 20-30 parts of polypropylene and 2-4 parts of anti-scratch agent, drying the weighed raw materials in an oven at 80° C. for 8 hours to remove the existing moisture, adding the materials into a twin-screw extruder and extruding, setting the parameters as the main screw speed of 200 r / min, the screw section temperature range of 170-190° C., and the head temperature of 205° C., and then granulating with a pelletizer to obtain a mixture 1;
[0023] Step S22, weighing 5-15 parts of phenolic resin and 0.05-0.2 parts of antibacterial additive, drying the weighed raw materials in an oven at 80°C for 8 hours to remove the existing moisture, adding the materials into a twin-screw extruder and extruding, setting the parameters as the main screw speed of 200r / min, the screw section temperature range of 170-190°C, the head temperature of 205°C, and then granulating with a pelletizer to obtain a mixture 2;
[0024] Step S23, uniformly mix the obtained mixtures 1 and 2 with 0.5 to 1 part of a silane coupling agent, melt at 170 to 190° C., granulate with a pelletizer, and inject with an injection molding machine to obtain a wear-resistant layer.
[0025] (III) Beneficial effects
[0026] The invention provides a composite material for automobile interior decoration parts and a preparation process thereof, which have the following beneficial effects: the composite material is composited by two layers of materials, the internal flame retardant layer improves the flame retardant performance of the material by adding a flame retardant, and the limiting oxygen index (LOI) of the flame retardant layer is tested to be 29.5-34.2, and the flame retardant performance reaches the V-0 flame retardant standard; the wear-resistant layer improves the wear resistance of polypropylene resin by adding an anti-scratch agent, and the expandable graphite in the anti-scratch agent not only improves the wear resistance of the composite material, but also increases the flame retardant and antistatic effects, and the antibacterial property of the material is contributed by adding silver ions to the composite material. DETAILED DESCRIPTION
[0027] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0028] The polypropylene fiber used in the present invention has a polypropylene melt flow rate of 28 g / 10 min and is purchased from Sinopec, the glass fiber is purchased from Jiangsu Qiangsheng Functional Chemical Co., Ltd., the phenolic resin is purchased from Shanghai Pushun Import and Export Co., Ltd., the silane coupling agent trade name is KH550, KH560, KH570, purchased from Nanjing Lianye Chemical Co., Ltd., α-phase nano-alumina is purchased from Jiangsu Jingjing New Materials Co., Ltd., lignin is purchased from Hangzhou Dingyan Chemical Co., Ltd., expanded graphite, inorganic mineral powder, aluminum nitride, silicon powder are purchased from Jiacheng Industrial Co., Ltd., and sodium carboxymethyl cellulose is purchased from Shanghai Zhitong Chemical Co., Ltd.
[0029] Example 1
[0030] The present invention provides a technical solution: a composite material for automobile interior decoration parts, the composite material is composited by two layers of materials, including an inner flame retardant layer and an outer wear-resistant layer, the flame retardant layer and the wear-resistant layer are connected by a coating, the flame retardant layer material includes the following components by mass: 20-40 parts of polypropylene fiber, 10-30 parts of modified polypropylene, 5-10 parts of glass fiber, 1-3 parts of flame retardant, 1-3 parts of deionized water, and 0.1-0.5 parts of antioxidant; the wear-resistant layer includes the following components by mass: 20-30 parts of polypropylene, 5-15 parts of phenolic resin, α-phase nano-alumina, 2-4 parts of anti-scratch agent, 0.5-1 part of silane coupling agent, and 0.05-0.2 parts of antibacterial additive.
[0031] Furthermore, the thickness of the flame retardant layer is 1 to 5 mm, the thickness of the wear-resistant layer is 2 to 5 mm, and the connecting layer is an amino resin coating.
[0032] Furthermore, the flame retardant comprises the following components by mass: 20-40 parts of lignin, 5-10 parts of expanded graphite, and 5-10 parts of inorganic mineral powder, wherein the inorganic mineral powder comprises one of calcium carbonate, aluminum carbonate, potassium bicarbonate, and magnesium carbonate.
[0033] Furthermore, the modified polypropylene is modified by using polypropylene as a base material, aluminum nitride and silicon powder as nucleating agents, and sodium carboxymethyl cellulose as a thickener, and the modification process includes the following steps:
[0034] Step S01, weighing raw materials, weighing 40-50 parts of polypropylene, 1-3 parts of aluminum nitride, 1-1.5 parts of silicon powder, and 0.1-0.3 parts of sodium carboxymethyl cellulose, wherein the particle sizes of the aluminum nitride, silicon powder, and sodium carboxymethyl cellulose are 2-20 μm;
[0035] Step S02, pretreatment of raw materials: drying the weighed raw materials in an oven at 80° C. for 8 h to remove the existing moisture;
[0036] Step S03, uniformly mixing the prepared polypropylene material with the dried nucleating agent and thickener, and after the samples are uniformly mixed, melt blending is performed in a twin-screw extruder, and extrusion granulation is performed, and injection molding is performed at 200° C. to obtain a modified polypropylene material.
[0037] Furthermore, the antioxidant is Si powder, Al powder and B4C, or one of B4C, ZrB2, CaB6, LaB6, MgB2 and AlB2.
[0038] Furthermore, the anti-scratch agent comprises the following components by weight: 5 to 10 parts of silicone masterbatch, 2 to 3 parts of graphene, and 1 to 3 parts of polysiloxane; and the antibacterial auxiliary agent is silver ions.
[0039] The present invention provides a technical solution: a process for preparing a composite material for automobile interior decoration parts, wherein the preparation of the composite material comprises the following steps:
[0040] Step S11, preparing a flame retardant layer: weighing 20-40 parts of polypropylene fiber, 10-30 parts of modified polypropylene, 5-10 parts of glass fiber, 1-3 parts of flame retardant, 1-3 parts of deionized water, and 0.1-0.5 parts of antioxidant, mixing them evenly with a high-speed mixer, and then extruding and granulating them with a twin-screw extruder at 190-220° C., and injection molding them at 200° C. to obtain a sheet material 1;
[0041] Step S12, preparing a wear-resistant layer, weighing 20-30 parts of polypropylene, 5-15 parts of phenolic resin, α-phase nano-alumina, 2-4 parts of anti-scratch agent, 0.5-1 part of silane coupling agent, 0.05-0.2 parts of antibacterial additive, and then extruding and granulating them through a twin-screw extruder at 170-190° C., and injection molding at 180° C. to obtain a sheet material 2;
[0042] Step S13, compounding the flame retardant layer and the wear resistant layer: take the sheet materials 1 and 2, apply an amino resin coating on the connection between the materials, and press them together using a tablet press to obtain a composite material.
[0043] Furthermore, the wear-resistant layer comprises the following steps:
[0044] Step S21, weighing 20-30 parts of polypropylene and 2-4 parts of anti-scratch agent, drying the weighed raw materials in an oven at 80° C. for 8 hours to remove the existing moisture, adding the materials into a twin-screw extruder and extruding, setting the parameters as the main screw speed of 200 r / min, the screw section temperature range of 170-190° C., and the head temperature of 205° C., and then granulating with a pelletizer to obtain a mixture 1;
[0045] Step S22, weighing 5-15 parts of phenolic resin and 0.05-0.2 parts of antibacterial additive, drying the weighed raw materials in an oven at 80°C for 8 hours to remove the existing moisture, adding the materials into a twin-screw extruder and extruding, setting the parameters as the main screw speed of 200r / min, the screw section temperature range of 170-190°C, the head temperature of 205°C, and then granulating with a pelletizer to obtain a mixture 2;
[0046] Step S23, uniformly mix the obtained mixtures 1 and 2 with 0.5 to 1 part of a silane coupling agent, melt at 170 to 190° C., granulate with a pelletizer, and inject with an injection molding machine to obtain a wear-resistant layer.
[0047] Example 2
[0048] The present invention provides a technical solution: a process for preparing a composite material for automobile interior decoration parts, wherein the preparation of the composite material comprises the following steps:
[0049] Step S11, preparing a flame retardant layer: weighing 30 parts of polypropylene fiber, 30 parts of modified polypropylene, 10 parts of glass fiber, 1 part of flame retardant, 2 parts of deionized water, and 0.3 parts of antioxidant, mixing them evenly with a high-speed mixer, and then extruding and granulating them with a twin-screw extruder at 190-220° C., and injection molding them at 200° C. to obtain a sheet material 1;
[0050] Step S12, preparing a wear-resistant layer, weighing 30 parts of polypropylene, 5 parts of phenolic resin, α-phase nano-alumina, 3 parts of anti-scratch agent, 0.5-1 part of silane coupling agent, 0.05-0.2 parts of antibacterial additive, and then extruding and granulating them through a twin-screw extruder at 170-190° C., and injection molding at 180° C. to obtain a sheet material 2;
[0051] Step S13, compounding the flame retardant layer and the wear resistant layer: take the sheet materials 1 and 2, apply an amino resin coating on the connection between the materials, and press them together using a tablet press to obtain a composite material.
[0052] Example 3
[0053] The present invention provides a technical solution: a process for preparing a composite material for automobile interior decoration parts, wherein the preparation of the composite material comprises the following steps:
[0054] Step S11, preparing a flame retardant layer: weighing 30 parts of polypropylene fiber, 30 parts of modified polypropylene, 10 parts of glass fiber, 2 parts of flame retardant, 2 parts of deionized water, and 0.3 parts of antioxidant, mixing them evenly with a high-speed mixer, and then extruding and granulating them with a twin-screw extruder at 190-220° C., and injection molding them at 200° C. to obtain a sheet material 1;
[0055] Step S12, preparing a wear-resistant layer, weighing 30 parts of polypropylene, 5 parts of phenolic resin, 3 parts of α-phase nano-alumina, anti-scratch agent, 0.5-1 part of silane coupling agent, 0.05-0.2 part of antibacterial additive, and then extruding and granulating at 170-190° C. through a twin-screw extruder, and injection molding at 180° C. to obtain a sheet material 2;
[0056] Step S13, compounding the flame retardant layer and the wear resistant layer: take the sheet materials 1 and 2, apply an amino resin coating on the connection between the materials, and press them together using a tablet press to obtain a composite material.
[0057] Example 4
[0058] The present invention provides a technical solution: a process for preparing a composite material for automobile interior decoration parts, wherein the preparation of the composite material comprises the following steps:
[0059] Step S11, preparing a flame retardant layer: weighing 30 parts of polypropylene fiber, 30 parts of modified polypropylene, 10 parts of glass fiber, 2 parts of flame retardant, 2 parts of deionized water, and 0.3 parts of antioxidant, mixing them evenly with a high-speed mixer, and then extruding and granulating them with a twin-screw extruder at 190-220° C., and injection molding them at 200° C. to obtain a sheet material 1;
[0060] Step S12, preparing a wear-resistant layer, weighing 30 parts of polypropylene, 5 parts of phenolic resin, α-phase nano-alumina, 4 parts of anti-scratch agent, 0.5-1 part of silane coupling agent, 0.05-0.2 parts of antibacterial additive, and then extruding and granulating them through a twin-screw extruder at 170-190° C., and injection molding at 180° C. to obtain a sheet material 2;
[0061] Step S13, compounding the flame retardant layer and the wear resistant layer: take the sheet materials 1 and 2, apply an amino resin coating on the connection between the materials, and press them together using a tablet press to obtain a composite material.
[0062] Example 5
[0063] The present invention provides a technical solution: a process for preparing a composite material for automobile interior decoration parts, wherein the preparation of the composite material comprises the following steps:
[0064] Step S11, preparing a flame retardant layer: weighing 30 parts of polypropylene fiber, 30 parts of modified polypropylene, 10 parts of glass fiber, 3 parts of flame retardant, 2 parts of deionized water, and 0.3 parts of antioxidant, mixing them evenly with a high-speed mixer, and then extruding and granulating them with a twin-screw extruder at 190-220° C., and injection molding them at 200° C. to obtain a sheet material 1;
[0065] Step S12, preparing a wear-resistant layer, weighing 30 parts of polypropylene, 5 parts of phenolic resin, α-phase nano-alumina, 4 parts of anti-scratch agent, 0.5-1 part of silane coupling agent, 0.05-0.2 parts of antibacterial additive, and then extruding and granulating them through a twin-screw extruder at 170-190° C., and injection molding at 180° C. to obtain a sheet material 2;
[0066] Step S13, compounding the flame retardant layer and the wear resistant layer: take the sheet materials 1 and 2, apply an amino resin coating on the connection between the materials, and press them together using a tablet press to obtain a composite material.
[0067] Experimental example
[0068] The flame retardant properties of the flame retardant layer were verified by tests, wherein the limiting oxygen index test was based on GB / T2406.2-2009 "Plastic Combustion Performance Test Method Oxygen Index Method", and the flame retardancy was based on GB / T2408-2008 "Plastic Combustion Performance Determination Horizontal and Vertical Method Standards", and the results are shown in Table 1 as follows:
[0069] Table 1: Flame retardant properties of the flame retardant layer
[0070]
[0071]
[0072] The mechanical properties and scratch resistance of the wear-resistant layer are verified by experiments. In the mechanical properties test, the tensile strength is measured with reference to the method in GB / T1040.1-2018 "Determination of tensile properties of plastics Part 1: General principles", the flexural strength is measured with reference to the method in GB / T9341-2008 "Determination of flexural properties of plastics", and the Izod notched impact strength is measured using a cantilever beam impact testing machine with reference to the method in GB / T1043.1-2008 "Hard Plastic Simple Supported Beam Impact Test Method"; the scratch resistance test is carried out with reference to the method in the German Volkswagen standard "Plastic Interior Scratch Resistance Test" to measure the scratch resistance of the wear-resistant layer sample. A scratch head with a diameter of 1.0 mm was selected, the scratch load was 10 N, the scratch speed was 1000 mm / min, the scratch spacing was 2 mm, the scratch length was 40 mm, 20 scratches were made in the longitudinal and transverse directions of the sample, and the color difference value before and after the sample was scratched was measured with a colorimeter. The wear-resistant layer and the flame-retardant layer obtained in Examples 2 to 4 were tested, and the results are shown in Table 2:
[0073] Table 2: Mechanical properties and scratch resistance of wear-resistant layer
[0074]
[0075] In summary, the composite material is composed of two layers of materials. The internal flame retardant layer improves the flame retardant properties of the material by adding flame retardants. After testing, the limiting oxygen index (LOI) of the flame retardant layer is 29.5-34.2, and the flame retardant property reaches the V-0 flame retardant standard; the wear-resistant layer improves the wear resistance of the polypropylene resin by adding an anti-scratch agent. The expandable graphite in the anti-scratch agent not only improves the wear resistance of the composite material, but also increases the flame retardant and antistatic effects. By adding silver ions to the composite material, the antibacterial property of the material is improved, which solves the problem of poor flame retardancy and poor wear resistance of existing automotive interior composite materials.
[0076] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A composite material for automotive interior parts, characterized in that: The composite material is composed of two layers of materials, including an inner flame retardant layer and an outer wear-resistant layer. The flame retardant layer and the wear-resistant layer are connected by a coating. The flame retardant layer material includes the following components by mass: 20 to 40 parts of polypropylene fiber, 10 to 30 parts of modified polypropylene, 5 to 10 parts of glass fiber, 1 to 3 parts of flame retardant, 1 to 3 parts of deionized water, and 0.1 to 0.5 parts of antioxidant. The wear-resistant layer includes the following components by mass: 20 to 30 parts of polypropylene, 5 to 15 parts of phenolic resin, 2 to 4 parts of anti-scratch agent, 0.5 to 1 part of silane coupling agent, 0.05 to 0.2 parts of antibacterial additive, and α-phase nano-alumina.
2. The composite material for automobile interior decoration according to claim 1, characterized in that: The thickness of the flame retardant layer is 1 to 5 mm, the thickness of the wear-resistant layer is 2 to 5 mm, and the connecting layer is an amino resin coating.
3. The composite material for automobile interior parts according to claim 1, characterized in that: The flame retardant comprises the following components by weight: 20-40 parts of lignin, 5-10 parts of expanded graphite, and 5-10 parts of inorganic mineral powder, wherein the inorganic mineral powder comprises one of calcium carbonate, aluminum carbonate, potassium bicarbonate, and magnesium carbonate.
4. The composite material for automobile interior decoration according to claim 1, characterized in that: The modified polypropylene is based on polypropylene, aluminum nitride and silicon powder are used as nucleating agents, and sodium carboxymethyl cellulose is used as a thickener for modification. The modification process includes the following steps: Step S01, weighing raw materials, weighing 40-50 parts of polypropylene, 1-3 parts of aluminum nitride, 1-1.5 parts of silicon powder, and 0.1-0.3 parts of sodium carboxymethyl cellulose, wherein the particle sizes of the aluminum nitride, silicon powder, and sodium carboxymethyl cellulose are 2-20 μm; Step S02, pretreatment of raw materials: drying the weighed raw materials in an oven at 80° C. for 8 h to remove the existing moisture; Step S03, uniformly mixing the prepared polypropylene material with the dried nucleating agent and thickener, and after the samples are uniformly mixed, melt blending is performed in a twin-screw extruder, and extrusion granulation is performed, and injection molding is performed at 200° C. to obtain a modified polypropylene material.
5. The composite material for automobile interior parts according to claim 1, characterized in that: The antioxidant is Si powder, Al powder and B4C, or one of B4C, ZrB2, CaB6, LaB6, MgB2 and AlB2.
6. The composite material for automobile interior decoration according to claim 1, characterized in that: The anti-scratch agent comprises the following components by weight: 5 to 10 parts of silicone masterbatch, 2 to 3 parts of expandable graphite, and 1 to 3 parts of polysiloxane; the antibacterial auxiliary agent is silver ions.
7. A process for preparing a composite material for automobile interior decoration parts according to any one of claims 1 to 6, characterized in that: The preparation of the composite material comprises the following steps: Step S11, preparing a flame retardant layer: weighing 20-40 parts of polypropylene fiber, 10-30 parts of modified polypropylene, 5-10 parts of glass fiber, 1-3 parts of flame retardant, 1-3 parts of deionized water, and 0.1-0.5 parts of antioxidant, mixing them evenly with a high-speed mixer, and then extruding and granulating them with a twin-screw extruder at 190-220° C., and injection molding them at 200° C. to obtain a sheet material 1; Step S12, preparing a wear-resistant layer, weighing 20-30 parts of polypropylene, 5-15 parts of phenolic resin, α-phase nano-alumina, 2-4 parts of anti-scratch agent, 0.5-1 part of silane coupling agent, 0.05-0.2 parts of antibacterial additive, and then extruding and granulating them through a twin-screw extruder at 170-190° C., and injection molding at 180° C. to obtain a sheet material 2; Step S13, compounding the flame retardant layer and the wear resistant layer: take the sheet materials 1 and 2, apply an amino resin coating on the connection between the materials, and press them together using a tablet press to obtain a composite material.
8. The process for preparing a composite material for automobile interior parts according to claim 7, characterized in that: The wear-resistant layer comprises the following steps: Step S21, weighing 20-30 parts of polypropylene and 2-4 parts of anti-scratch agent, drying the weighed raw materials in an oven at 80° C. for 8 hours to remove the existing moisture, adding the materials into a twin-screw extruder and extruding, setting the parameters as the main screw speed of 200 r / min, the screw section temperature range of 170-190° C., and the head temperature of 205° C., and then granulating with a pelletizer to obtain a mixture 1; Step S22, weighing 5-15 parts of phenolic resin and 0.05-0.2 parts of antibacterial additive, drying the weighed raw materials in an oven at 80°C for 8 hours to remove the existing moisture, adding the materials into a twin-screw extruder and extruding, setting the parameters as the main screw speed of 200r / min, the screw section temperature range of 170-190°C, the head temperature of 205°C, and then granulating with a pelletizer to obtain a mixture 2; Step S23, uniformly mix the obtained mixtures 1 and 2 with 0.5 to 1 part of a silane coupling agent, melt at 170 to 190° C., granulate with a pelletizer, and inject with an injection molding machine to obtain a wear-resistant layer.
Citation Information
Patent Citations
Energy-saving eco-friendly novel automobile and motorcycle internal decorating material and manufacturing method thereof
CN105479894A
Novel wear-resistant and flame-retardant wood-plastic floor and preparation method thereof
CN106003882A
Multi-layer structurally strengthened composite car carpet
CN106079798A
Green intumescent flame retardant polypropylene and preparation method thereof
CN110564058A
Polypropylene composition containing nucleating agent, modified polypropylene and preparation method thereof
CN112194848A